Knowledge, attitude, and practice of osteoporosis prevention in elder patients following lumbar fusion surgery: a cross‐sectional study - Sheng, Shaoying; Wang, Manman; Yu, Chengfei; Li, Qing; Wang, Zhan; Ma, Yaojing (Frontiers in Aging, 2025)
PurposeTo assess the knowledge, attitudes, and practices (KAP) regarding osteoporosis prevention among older adult patients following lumbar fusion surgery and identify associated factors.Patients and methodsA cross-sectional study was conducted with participants aged ≥50 years. Data on demographic characteristics, KAP related to osteoporosis prevention, and lifestyle behaviors were collected using structured questionnaires. Chi-square tests were performed to explore associations between demographic variables and knowledge levels.ResultsA total of 217 participants were included in the study. Participants demonstrated varying levels of knowledge, with 28.6% scoring high on the OPAAT. Female gender, higher educational attainment, urban residence, and diabetes were significantly associated with higher knowledge levels. Positive lifestyle practices, such as calcium and vitamin D supplementation, were observed in 64.5% and 41.0% of participants, respectively, while regular outdoor exercise and dairy product consumption were less common.ConclusionThe findings highlight gaps in osteoporosis prevention KAP among older adult patients following lumbar fusion surgery. Tailored educational programs and interventions are necessary to enhance awareness and promote healthier behaviors.